Unraveling synonymous and deep intronic variants causing aberrant splicing in two genetically undiagnosed epilepsy families - Qiang Li; Yiting Wang; Yijun Pan; Jia Wang; Weishi Yu; Xiaodong Wang (BMC, 2021)
Abstract Background Variants identified through parent-child trio-WES yield up to 28-55% positive diagnostic rate across a variety of Mendelian disorders, there remain numerous patients who do not receive a genetic diagnosis. Studies showed that some aberrant splicing variants, which are either not readily detectable by WES or could be miss-interpreted by regular detecting pipelines, are highly relevant to human diseases. Methods We retrospectively investigated the negative molecular diagnostics through trio-WES for 15 genetically undiagnosed patients whose clinical manifestations were highly suspected to be genetic disorders with well-established genotype-phenotype relationships. We scrutinized the synonymous variants from WES data and Sanger sequenced the suspected intronic region for deep intronic variants. The functional consequences of variants were analyzed by in vitro minigene experiments. Results Here, we report two abnormal splicing events, one of which caused exon truncating due to the activation of cryptic splicing site by a synonymous variant; the other caused partial intron retention due to the generation of splicing sites by a deep intronic variant. Conclusions We suggest that, despite initial negative genetic test results in clinically highly suspected genetic diseases, the combination of predictive bioinformatics and functional analysis should be considered to unveil the genetic etiology of undiagnosed rare diseases.